(untitled) (Ustozlar uchun, 2026)
The referee’s final whistle blew. The thirty-year longing on the pitch, the trembling in millions of hearts, and the long wait of an entire nation rose to the sky as one immense cry. Uzbekistan is in the World Cup! Football is not merely twenty-two people chasing a ball on a green field. It is the mood of the people, their psychology, a space for self-realization, and, most importantly, the power of uniting around a single goal. For the first time in history, the Uzbekistan national football team secured a ticket to our planet’s most prestigious tournament — the FIFA World Cup. This is an unprecedented event and a historical turning point not only for our country but for the entire Central Asian region. Until now, no country in our region had been able to conquer this milestone. This event is a vivid manifestation of the will of our hardworking, patient, and never-surrendering people. The flags waving in the streets, the tears in people’s eyes, and the boundless sense of pride in their hearts have united the whole country like a single fist today. This victory has shown the whole world what kind of power we possess on the global stage.